Abu-Lughod, Lila, Do Muslim Women Need Saving?, Cambridge, Harvard University Press, 2013, 336 pp. - Castro Méndez, Evelyn Norma (Estudios de Asia y África, 2014)
Abu-Lughod, Lila, Do Muslim Women Need Saving?, Cambridge, Harvard University Press, 2013, 336 pp.